Prediksi Tren Risiko Keuangan Perusahaan Berdasarkan Model Machine Learning (ARIMA) : Tinjauan Literatur - Sunaryo, Deni; Hamdan; Anggriani, Alfina; Winata, Cecilia; Alumi, Dian Denta (Universitas Serang Raya, 2024)
This research discusses the role of artificial intelligence (AI) technology in improving company financial risk predictions through the application of the Autoregressive Integrated Moving Average (ARIMA) model supported by machine learning. Using systematic literature analysis, this research explores how ARIMA, with the help of AI, can be applied in financial risk management to identify short-term and long-term trends, detect financial anomalies, and improve the quality of decision making. ARIMA models based on machine learning enable faster and more accurate identification of abnormal financial patterns, which is very important in helping companies respond to risks that have the potential to disrupt financial stability. Key findings show that the combination of ARIMA and AI not only makes it easier to analyze large and complex financial data, but also expands the potential of data-driven financial risk management by providing deeper insights. By integrating machine learning, ARIMA becomes more effective in handling dynamic and fluctuating financial data, so companies can anticipate risks more proactively. This study underscores the enormous potential of AI and ARIMA in helping companies build adaptive, high-precision risk prediction systems, offering new opportunities to strengthen financial resilience in an ever-changing business environment.